Glycosyltransferase-Like RSE1 Negatively Regulates Leaf Senescence Through Salicylic Acid Signaling in Arabidopsis - Lee, Seulbee; Kim, Myung-Hee; Lee, Jae Ho; Jeon, Jieun; Kwak, June M.; Kim, Yun Ju (Frontiers in Plant Science, 2020)
Leaf senescence is a developmental process designed for nutrient recycling and relocation to maximize growth competence and reproductive capacity of plants. Thus, plants integrate developmental and environmental signals to precisely control senescence. To genetically dissect the complex regulatory mechanism underlying leaf senescence, we identified an early leaf senescence mutant, rse1. RSE1 encodes a putative glycosyltranferase. Loss-of-function mutations in RSE1 resulted in precocious leaf yellowing and up-regulation of senescence marker genes, indicating enhanced leaf senescence. Transcriptome analysis revealed that salicylic acid (SA) and defense signaling cascades were up-regulated in rse1 prior to the onset of leaf senescence. We found that SA accumulation was significantly increased in rse1. The rse1 phenotypes are dependent on SA-INDUCTION DEFICIENT 2 (SID2), supporting a role of SA in accelerated leaf senescence in rse1. Furthermore, RSE1 protein was localized to the cell wall, implying a possible link between the cell wall and RSE1 function. Together, we show that RSE1 negatively modulates leaf senescence through an SID2-dependent SA signaling pathway.